Research and analysis of traction converter for EMU based on MBSE - WANG Baomin; YANG Jiuhe; ZHOU Jinxiang; WANG Haifang; CHE Jun (机车电传动)
This paper focuses on applying model-based systems engineering (MBSE) methodology to the design of EMU traction converters, to address challenges stemming from an abundance of information and complexities in modification. The study initially uncovered the whole life cycle process of EMU traction converters, leveraging the modeling language SysML and the modeling tool Magic Draw, and concentrated on modeling the design stage based on an analysis digging into requirements. The requirements of traction converters were categorized into non-functional requirements and functional ones during the modeling process. The non-functional requirements were analyzed to assess the impact of environmental factors on the operation of EMU traction converters, and were verified through simulations incorporating diagrams of requirements and parameters created using the modeling tool Magic Draw. The analysis of functional requirements focused on the current regulation function of traction converters, through creating activity diagrams and timing diagrams. The subsequent analysis delved into the traction converter subsystems and presented the traction converter architecture by creating corresponding module definition diagrams and internal module diagrams. Additionally, a traceability matrix was established to ensure no omission in the functional analysis. The study findings endorse the application of the MBSE methodology, particularly through model correlations, as an effective solution to challenges in the design of EMU traction converters, such as complexities in information search and modifications in the traditional document-based mode. Hence, the proposed approach effectively facilitates the transformation of internal design information of traction converters from a textual representation to a model-based format.